Fake online news: Rethinking news credibility for the changing media environment - Adikpo, Janet Aver (IGI Global, 2020)
Today, the media environment has traversed several phases of technological advancements and as a result, there is a shift in the production and consumption of news. This chapter conceived fake news within the milieu of influencing information spread in the society, especially on the cyberspace. Using the hierarchy of influence model trajectory with fake news, it was established that it has become almost impossible to sustain trust and credibility through individual influences on online news content. The primary reason is that journalists are constrained by professional ethics, organizational routines, and ownership influence. Rather than verify facts and offer supporting claims, online users without professional orientation engage in a reproducing information indiscreetly. The chapter recommends that ethics be reconsidered as a means to recreate and imbibe journalistic values that will contend with the fake news pandemic. © 2021, IGI Global.